European Projects to Support Ukrainian Scientists in Conditions of Forced Migration during Martial law in 2022-2024 - Hryhorevska, Olena (Naukovi prat͡s︡i Nat͡s︡ionalʹnoï biblioteky Ukraïny imeni V.I. Vernadsʹkoho, 2024)
The purpose of the article is to analyse European projects in support Ukrainian scientists’ research activities during the Russian-Ukrainian war. The research methodology is based on the integrated application of a sociocommunication approach combined with a systemic, structural-functional approach. The set of research methods includes methods of systematic analysis, content analysis of scientific publications and resources of institutions’ and projects’ websites, expert observation, synthesis and generalisation. Scientific novelty. For the first time, the subject of the study was to identify common and distinctive features, peculiarities of the institutional organisation of two global international projects - the MSCA4 Ukraine project, implemented with the support of the European Union, the international project Sc!ence at R!sk! and the local project HelpUkraine, implemented by the Vrije Universiteit Brussel (Kingdom of Belgium) in 2022-2023. Conclusions. The projects presented in this study are aimed at achieving a common goal - to provide assistance and support to Ukrainian scientists, educators and students who, as a consequence of Russian military aggression, have found themselves unable to carry out their professional activities in the dangerous conditions. The study we have presented is only the first attempt to outline the differences and peculiarities in implementing such projects, which are different in scale and results. Their implementation is ongoing. The MSCA4 Ukraine scholarship programme makes a great contribution not only to the personal development of the scholars who have won it, but also helps to determine the future of Ukrainian science and education in the long-term perspective of post war recovery. The Humboldt Foundation (a member of the project consortium) initiated a discussion on the future of science and academia in Ukraine, which resulted in the identification of key positions to support researchers who remain in Ukraine, improve the working conditions of researchers on a long-term basis, create centres of excellence, and facilitate Ukraine’s rapid accession to the European Research Area. The international project Sc!ence at R!sk!, which is both a digital platform and a scientific community, aims to develop multidirectional policies for the post-war restoration of research activity in Ukraine and to help Ukrainian scientists affected by the war. The analytical work of the project participants contributes to bringing the anti-crisis experience of preserving Ukrainian science to the international community, attracting the experience of other countries that can be followed in order to restore Ukrainian science after the war. The HelpUkraine project of the Vrije Universiteit Brussel, which we have designated as “local”, i.e. focused on one country and one university, deserves further study in comparison with other similar projects that continue to be implemented by European universities. This type of project is characterised by a variety of impact vectors and forms of implementation, the involvement of a wide range of public initiatives and opportunities for socio-cultural development, and support for participants. Each of these projects, each of the partners, organisers and participants adds its voice to the formation of sound global policy to better protect educators and researchers in difficult circumstances, and contributes to increasing respect for academic freedom around the world.